Nilai – Nilai Yang Terkandung Dalam Implementasi Budaya Kyuushoku ( Makan Siang di Sekolah ) - Yuli Krisanthi Komang; Wayan Wahyu Cipta Widiastika (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2024)
In Japan, education and culture are highly respected, leading to various systems in education that encourage learning not only focused on teaching and learning itself. Education in Japan emphasizes character development and social attitudes towards different cultures, as well as the formation of cultural identity. One such system is called Shokuiku, which is centered on learning about the origins of food, understanding nutritional values, and developing a positive relationship with food. Within Shokuiku, there is a school lunch program called Kyuushoku. The role of school lunches in the overall educational system opens a deeper dimension to explore how food education and culture interrelate and shape a unique cultural identity. Therefore, this research aims to understand the values contained in the implementation of Kyuushoku culture. The theory used in this research is the Structural Functional Theory according to Talcott Parsons. The methods employed by the author include library research and field studies, sending surveys via Google Forms online to the Japanese community that has participated in Kyuushoku as supporting data sources. The results of this study indicate that Kyuushoku culture carries values such as: Nutrition and Health, Cooperation and Helping Each Other, Togetherness, and Environmental Awareness.